Study protocol for the BRAIN Training Trial: a randomised controlled trial of Balance, Resistance, And INterval training on cognitive function in older adults with mild cognitive impairment - Teresa Liu-Ambrose; Ulrik Wisløff; Maria Fiatarone Singh; Yorgi Mavros; Perminder S Sachdev; Ryan S Falck; Dorthe Stensvold; Jeff S Coombes; Trinidad Valenzuela; Nicole Kochan; Wei Wen; Jeffrey Hausdorff; et al. (BMJ Open)
Introduction Epidemiological evidence suggests that both poor cardiovascular fitness and low muscle mass or strength markedly increase the rate of cognitive decline and incident dementia in older adults. Results from exercise trials for the improvement of cognition in older adults with mild cognitive impairment (MCI) have reported mixed results. This is possibly due to insufficient exercise intensities. The aim of the Balance, Resistance, And INterval (BRAIN) Training Trial is to determine the effects of two forms of exercise, high-intensity aerobic interval training (HIIT) and high-intensity power training (POWER) each compared with a sham exercise control group on cognition in older adults with MCI.Methods and analysis One hundred and sixty community-dwelling older (≥ 60 years) people with MCI have been randomised into the trial. Interventions are delivered supervised 2–3 days per week for 12 months. The primary outcome measured at baseline, 6 and 12 months is performance on a cognitive composite score measuring the executive domain calculated from a combination of computerised (NeuroTrax) and paper-and-pencil tests. Analyses will be performed via repeated measures linear mixed models and generalised linear mixed models of baseline, 6-month and 12-month time points, adjusted for baseline values and covariates selected a priori. Mixed models will be constructed to determine the interaction of GROUP × TIME.Ethics and dissemination Ethical approval was obtained from the University of Sydney (HREC Ref.2017/368), University of Queensland (HREC Ref. 2017/HE000853), University of British Columbia (H16-03309), and Vancouver Coastal Health Research Institute (V16-03309) Human Research Ethics. Dissemination will be via publications, conference presentations, newsletter articles, social media, talks to clinicians and consumers and meetings with health departments/managers.It is expected that communication of results will allow for the development of more effective evidence-based exercise prescription guidelines in this population while investigating the benefits of HIIT and POWER on subclinical markers of disease.Trial registration number ACTRN12617001440314 Australian New Zealand Clinical Trials Registry.